1984
DOI: 10.1210/endo-114-1-240
|View full text |Cite
|
Sign up to set email alerts
|

The Actions of Insulin-Like Growth Factors I and II on Cultured Sertoli Cells*

Abstract: Cultured Sertoli cells prepared from young rats (13 days old) showed increased incorporation of [3H]thymidine into DNA, increased production of lactate, and increased incorporation of [3H]leucine into protein in response to micromolar concentrations of insulin and nanomolar concentrations of insulin-like growth factor II (IGF-II). The first of these responses was also seen with nanomolar concentrations of IGF-I. Receptor affinity labeling studies using Sertoli cell membranes and whole Sertoli cells showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(83 citation statements)
references
References 12 publications
5
78
0
Order By: Relevance
“…Within the testis the Sertoli cell has been proposed to be a site of IGF-I production (39), reception (40) and action (41,42) as well as of IGFBP generation (43). The intratesticular IGF system appears to be under a complex regulation by endocrine and paracrine factors (16) not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Within the testis the Sertoli cell has been proposed to be a site of IGF-I production (39), reception (40) and action (41,42) as well as of IGFBP generation (43). The intratesticular IGF system appears to be under a complex regulation by endocrine and paracrine factors (16) not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…8) (Lin et al, 1986a, b) in rat Leydig cells. The presence of Sm-C/IGF-I receptors in immature rat Sertoli cells has also been reported (Borland et al, 1984 ;Oonk and Grootegoed, 1987a,b), but contradictory results were obtained concerning insulin receptors. Borland et al (1984) could not demonstrate such receptors in immature cultured rat Sertoli cells and in that model insulin at nanomolar concentrations had no biological effect.…”
mentioning
confidence: 80%
“…Lactate production in Sertoli cells has been shown to be under the control of folliclestimulating hormone (FSH) (3), insulin, insulin-like growth factor-I (IGF-I) and IGF-II (4,5), transforming growth factor-b (TGFb) (6) and, more recently, it has been shown that tumor necrosis factor-a (TNFa) is also involved in its production (7). Reduced glutathione is a powerful scavenger of reactive oxygen species and toxic chemicals, which is used by many tissues in the detoxification of electrophilic compounds and cellular protection against oxidative stress (8,9).…”
Section: Introductionmentioning
confidence: 99%